Ecological Orientation of Law – Reviving Ancient Concepts in Contemporary Thought - Joldžić, Vladan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2009)
Text "Ecological orientation of law – reviving of ancient concepts in actual thought" analyses ancient philosophical reflection connected with ecological problems, works of Apolodor, Hrisip, Zeno of Elea, Plato and Aristotle, and their influence on actual intellectual ecological concepts. Of course, at the law concepts and legislative efforts are expressed at the levels of states and, at the same time, at the level of the international community, forming a logical and formal legal base for developing the environmental penal law.